Treatment of allergic rhinitis in children: old problem, new solutions - L.V. Besh (Zaslavsky O.Yu., 2017)
The article deals with the problem of allergic rhinitis in children. The attention is paid to the problems in the treatment of this disease. It is emphasized that the most common and most problematic manifestation of allergic rhinitis is a swelling of the nasal mucosa, which blocks the nasal breathing. To relieve this symptom, it is pathogenetically justified to prescribe a preparation from topical corticosteroid group, for example, Ukrainian drug under the trade name Forinex. The data are given on the effectiveness of the use of Forinex in children aged 6-14 years with moderately severe allergic rhinitis.